Hybrid learning landscape framework: holistic high performance schools for comprehensive learning and play - Vickrey, Jaime (Kansas State University, 2011)
School environments of today’s urban children are generally inflexible, restricting and uninspiring places for learning and exploration that are disconnected from their surrounding community and nature. Facilities and teaching methods do not keep pace with the evolving needs of the workforce and varying child learning styles (Stanbury 2009). Organized sports, limited free time and standardized testing steal the zest out of childhood discovery once felt by children who grew up with a connection to their surroundings, especially nature. Many adverse effects are seen as a result. “Nature-deficit disorder describes the human costs of alienation from nature, among them: diminished use of the senses, attention difficulties and higher rates of physical and emotional illnesses,” (Louv 2008, 36). Children are left to face the world’s escalating environmental dilemmas with hindered social and cognitive skills, diseases related to association and disassociation from nature and an impaired relationship with their extended community. Programs like University Colorado Denver’s Learning Landscapes and California’s Collaborative for High Performance Schools (CHPS) and have individually worked to improve learning facilities, reconnect students with outdoor curriculum-based learning and establish a bond with their communities. But implemented designs reveal unmet potential, calling for advancement and further evolution of the school learning environment. MontClair Elementary in Oakland, California is a typical urban school with paved schoolyard, restricted boundary, weak link between curriculum and schoolyard, disconnect from the community and disassociation from nature. New CHPS verified facilities are being implemented on their existing campus to accommodate an increase in student population but the link between schoolyard and curriculum has only been minimally addressed in the proposed design. Integrating Learning Landscapes with the Collaborative for High Performance Schools to create a hybrid learning landscape framework will reconnect MontClair Elementary with the surrounding community and nature. Advancement of the CHPS program, through adaptation of their existing scorecard, will allow Hybrid Learning Landscape Framework to be quantitatively applied to MontClair Elementary.
Keywords: Learning landscape; Education; Elementary Education (0524); Environmental education (0442)